ANALISA KUALITAS BAHAN BAKAR JENIS PERTALITE DI SPBU DENGAN PERTALITE DI PERTAMINI BERDASARKAN PARAMETER UJI SPECIFIC GRAVITY, REID VAPOUR PRESSURE, DOCTORT TEST, DISTILASI, COPPER STRIP TEST, OCTANE NUMBER - Rahma Nuryanti; Dian Kurnia Sari; Inta Marlen Puspita Sari (Bajang Institute, 2023)
Pertalite is a type of fuel with 90-octane level which is used for four- wheeled and two-wheeled vehicles. This study compares the quality of Pertalite fuel at Gas Stations (SPBU) with Pertamina Mini (Pertamini). The aim of the research is to compare the quality of pertaline sold in different places. The parameters used in this research were specific gravity ASTM D-1298 which showed specific gravity 60/60